The Effect of Different Storage Conditions on the Levels of Bisphenol A in Bottled Drinking Water in Jeddah City, Saudi Arabia - Lina Baz; Asmaa Alharbi; Maryam Al-Zahrani; Sedra Alkhabbaz; Rasha Alsousou; Hanan Aljawadri (Hindawi Limited, 2023)
Bisphenol A (BPA) in drinking water sources is a significant concern in society because BPA is one of the endocrine disruption compounds (EDCs) that can cause hazards to human health even at extremely low concentration levels. This study investigated the leaching potential of BPA from drinking water bottles in five brands of bottled drinking water in Jeddah, Saudi Arabia, using high-performance liquid chromatography with a diode array detector (HPLC-DAD). To the best of our knowledge, this is the first study to evaluate the level of BPA in bottled water in the city of Jeddah. The separation was carried out under isocratic elution, and the detector was set to UV mode. Low levels of BPA were detected in all samples from polyethylene terephthalate (PET) containers. The mean concentration of BPA in water bottles stored at room temperature for 30 days was 9.46 ng·L−1, while the concentration of BPA in water bottles exposed to sunlight and boiling water bath was 16.13 ng·L−1 and 14.7 ng·L−1, respectively. Although the results show that the daily consumed concentration of BPA for an adult with 60 kg of body weight is 32.26 ng, which is lower than the total tolerable daily intake limit of BPA, health risks from the consumption of bottled water may increase after UV exposure for an extended time.